An Analysis Of Moral Values In Burnett’s Little Lord Fauntleroy Novel - Utami, Desfika Beti; Arini, Restu ((JELE) Journal Of English Language and Education, 2017)
This study deals with a novel entitled Little Lord Fauntleroy written by Frances Hodgson Burnett. The objectives of the study are: (1)to describe Cedric’s personality in the novel and (2)to reveal the moral values from Cedric’s personality in the novel. The study employed library study and descriptive qualitative analysis method. The data of the study are from the novel and other supporting documents. Based on the analysis, the writer found two things: firstly, Cedric is characterized as a boy who has good personalities such as honest, kind-hearted, friendly, humble, wise, sympathetic and responsible. Secondly, the moral values that can be taken from the novel are honesty, kindness, hospitality, modesty, wisdom, empathy and responsible.